Thioanisole ester based logic gate cascade to control ROS-triggered micellar degradation. Issue 16 (6th April 2022) - Piergentili, Irene; Bouwmans, Pepijn R.; Reinalda, Luuk; Lewis, Reece W.; Klemm, Benjamin; Liu, Huanhuan; de Kruijff, Robin M.; Denkova, Antonia G.; Eelkema, Rienk
Abstract : Thioanisole ester polymer side chains hydrolyze exclusively upon thioether oxidation, showing logic gate response. ROS-induced ester hydrolysis on the hydrophobic domain leads to nanocarrier disassembly with potential for targeted drug release. Abstract : In certain tumor and diseased tissues, reactive oxygen species (ROS), such as H2 O2, are produced in higher concentrations than in healthy cells. Drug delivery and release systems that respond selectively to the presence of ROS, while maintaining their stability in "healthy" biological conditions, have great potential as on-site therapeutics. This study presents polymer micelles with 4-(methylthio)phenyl ester functionalities as a ROS-responsive reactivity switch. Oxidation of the thioether moieties triggers ester hydrolysis, exposing a hydrophylic carboxylate and leading to micellar disassembly. At 37 °C, the micelles fall apart on a timescale of days in the presence of 2 mM H2 O2 and within hours at higher concentrations of H2 O2 (60–600 mM). In the same time frame, the nanocarriers show no hydrolysis in oxidant-free physiological or mildly acidic conditions. This logic gate cascade behavior represents a step forward to realize drug delivery materials capable of selective response to a biomarker input.